Mycophenolate mofetil versus cyclophosphamide for therapy of lupus nephritis: an evidence-based case report from systematic reviews and meta-analyses (Medical Journal of Indonesia, 2012)
Background: The aim of this case study is to compare the effectiveness between cyclophosphamide and mycophenolate mofetil to achieve remission of lupus nephritis in an evidence-based case report from meta-analyses. Methods: Method in this case study is evidence-based case report using meta-analyses. Clinical question used in this paper is; which immunosuppressant gives better result in achieving remission in lupus nephritis patient: cyclophosphamide or mycophenolate mofetil? To answer this question, we search the evidence from PubMed with the keywords: “lupus nephritis AND mycophenolate mofetil AND cyclophosphamide“ with inclusion criteria of meta-analysis, written in English, and focused comparing cyclophosphamide and mycophenolate mofetil. Results: From the searching method, we found 11 articles which is relevant. One has been excluded since it written in Hebrew, 4 articles excluded since are not focus answering the clinical question. At the end, 6 studies were included to the critical appraisal step. Conclusion: Based on the evidences, mycophenolate mofetil is non-inferior to cyclophosphamide in achieving remission in lupus nephritis patients, but with the better safety profile. Patient in our case study get mycophenolate mofetil and shows better clinical condition towards remission as she are evaluated in the outpatient clinic. (Med J Indones 2012;21:44-51) Keywords: Cyclophosphamide, evidence-based case report, lupus nephritis, meta-analysis, mycophenolate mofetil, remission, systematic review